2016
DOI: 10.1016/j.jbiomech.2016.03.055
|View full text |Cite
|
Sign up to set email alerts
|

Wide bandwidth nanomechanical assessment of murine cartilage reveals protection of aggrecan knock-in mice from joint-overuse

Abstract: Aggrecan loss in human and animal cartilage precedes clinical symptoms of osteoarthritis, suggesting that aggrecan loss is an initiating step in cartilage pathology. Characterizing early stages of cartilage degeneration caused by aging and overuse is important in the search for therapeutics. In this study, atomic force microscopy (AFM)-based force-displacement micromechanics, AFM-based wide bandwidth nanomechanics (nanodynamic), and histologic assessments were used to study changes in distal femur cartilage of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 27 publications
1
26
0
Order By: Relevance
“…To measure the complex modulus of samples over a wide frequency range (1 Hz to 10 kHz), we used our custom high-frequency rheology system coupled to a commercial atomic force microscope (AFM) (MFP-3D, Asylum Research, Santa Barbara, CA) (Azadi et al, 2016; Nia et al, 2013). We used polystyrene colloidal probe tips with varying diameters of ~4.5–50 μm (Polysciences, Warrington, PA) attached to tipless cantilevers with nominal spring constant k ~ 7.4 N/m (Budget Sensors, Sofia, Bulgaria).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…To measure the complex modulus of samples over a wide frequency range (1 Hz to 10 kHz), we used our custom high-frequency rheology system coupled to a commercial atomic force microscope (AFM) (MFP-3D, Asylum Research, Santa Barbara, CA) (Azadi et al, 2016; Nia et al, 2013). We used polystyrene colloidal probe tips with varying diameters of ~4.5–50 μm (Polysciences, Warrington, PA) attached to tipless cantilevers with nominal spring constant k ~ 7.4 N/m (Budget Sensors, Sofia, Bulgaria).…”
Section: Methodsmentioning
confidence: 99%
“…As tendons are primarily composed of water, about 75% of the wet weight, regulation of fluid flow is crucial to dynamic mechanical behavior. In articular cartilage, for example, the abundance of the large proteoglycan aggrecan is responsible for the tissue’s complex poroelastic properties (Azadi et al, 2016; Nia et al, 2015b, 2013, 2011). It has recently been shown that proteoglycan concentration and type can vary dramatically along and between tendons, and specifically that rotator cuff tendons contain aggrecan in addition to decorin and biglycan (Berenson et al, 1996; Matuszewski et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The magnitudes of joint loading, instability and initial structural damage required to classify models as “post‐traumatic” OA is currently ill defined, and requires clarification. However, it seems prudent to include this Type III classification, as it likely shares some of the pathophysiological mechanisms (e.g., biomechanical loading) of Type I and II, and may serve to shed light on risk factors for specific aspects of PTOA pathology and susceptibility, for example, exercise modifying OA in genetically modified mice . The boundary between physiological, protective, and sub‐critical damaging joint loading levels is not clear, and better defining the factors that might shift this balance in either direction in a given individual, would greatly benefit our understanding of what constitutes a joint “injury,” and its management to prevent the initiation and progression of OA.…”
Section: What Is Post‐traumatic Osteoarthritis (Ptoa)?mentioning
confidence: 99%
“…It has been long established that moderate mechanical loading by exercise benefits cartilage health and function by increasing cartilage thickness, proteoglycan content, and mechanical stiffness . However, nonphysiological loading such as overuse can lead to cartilage degradation . Proinflammatory cytokines and other mediators produced in joint tissues in response to nonphysiological loading play important roles in cartilage degradation and osteoarthritis (OA) pathogenesis .…”
Section: Introductionmentioning
confidence: 99%
“…4 However, nonphysiological loading such as overuse can lead to cartilage degradation. [5][6][7] Proinflammatory cytokines and other mediators produced in joint tissues in response to nonphysiological loading play important roles in cartilage degradation and osteoarthritis (OA) pathogenesis. [8][9][10][11] In particular, interleukin (IL)-1 and tumor necrosis factor-␣ can induce cartilage degradation 12 by upregulating matrix metalloproteinase (MMP) 13 gene expression in articular chondrocytes.…”
Section: Introductionmentioning
confidence: 99%